Agreement between veterinary patient data collected from different sources - Robinson, Natalie Jane; Brennan, Marnie L.; Cobb, Malcolm; Dean, Rachel S. (Elsevier, 2015)
Determining the accuracy of the electronic medical record (EMR) is vital to the progress of practice based research. The aim of this study was to determine the agreement between the EMR and other sources of signalment data. Data were gathered during direct observation of small animal consultations in eight veterinary practices. Breed, age, sex and neuter status were recorded, where available, from the EMR, owner and observer and then compared for agreement. Agreement was ‘almost perfect’ or ‘strong’ for 18/28 comparisons, although there was variation between the species. The results have implications for researchers collecting data from the EMR of first opinion practices. Future work could focus on the accuracy of other data obtained from the EMR.